Annual report 2017: CGIAR Research Program on Roots, Tubers and Bananas - CGIAR Research Program on Roots, Tubers and Bananas (CGIAR Research Program on Roots, Tubers and Bananas, 2018)
Evaluative and impact assessment studies document how the results obtained by RTB, its implementing centers and partners, contribute to the achievement of the SRF targets. The Independent Evaluation Arrangement (IEA) collated existing reports against the CGIAR results framework (IDO level). Based on this, RTB identified 20 studies completed in the last six years that provide evidence on the contribution to the targets linked with SLO 1 and SLO 2. Research areas covered are: 1) enhancement and conservation of genetic material, including the development of improved and biofortified varieties and the conservation of local biodiversity; 2) production and processing technologies; 3) management of pests and diseases; 4) promotion of inclusive value chains. Summaries are available in Table A-1.